Enhanced Oxygen Reduction Reactions and Stable Long-term Activity on TiO2-supported Dealloyed PtCu Nanoparticles in Acidic Aqueous Solutions. (27th July 2015) - Gunji, Takao; Sasaki, Kengo; Jeevagan, Arockiam John; Kaneko, Shingo; Tanabe, Toyokazu; Matsumoto, Futoshi
Abstract : Dealloyed PtCu nanoparticles (NPs) were prepared on titanium oxide (TiO2 ) surfaces with chemical reduction of Pt and Cu ion precursors using a reducing agent in an organic solvent containing TiO2, which was followed by an electrochemical dealloying process of potential cycling (-0.2~1.2 V vs. RHE). Dealloyed PtCu NPs/TiO2 shows higher and substantial electrocatalytic activities towards oxygen reduction reactions (ORR) compared to conventional carbon black-supported Pt NPs (Pt NPs/CB). The current densities at 0.9 V ( vs. RHE) were -4.0 and -2.0 mAcm -2 on dealloyed PtCu NPs/TiO2 and Pt NPs/CB, respectively.